Innate Anti-Candidal Immunity and Evasive Strategies. - Aliyu, M. , Sharif, A.A. , Getso, M.I. , Mohammed, Y. , Adamu, A.Y , Takalmawa, H.U., Daneji, M.I. , and Jibril, M.* (Sokoto Journal of Medical Laboratory Science)
Candidiasis, an opportunistic infection commonly caused by the polymorphic commensal fungal agent, Candida albicans yielding a spectrum of infection from mild superficial infection to invasive disseminated disease. The systemic candidiasis occurs widely among immunocompromised patients with mostly fatal outcomes. Candida survived with us from birth to death, predominantly in symbiotic settings on the skin and mucosal surfaces. But in the presence of compromised immune systems from varying causes or when the Candida trooped outside its usual confinement, then they become opportunistic and cause severe disease. The resultant systemic spread is expensive to manage, allowing short response time before conceding a mortal score. The systemic candidiasis carries high mortality even in the most advanced settings. Despite extensive research, candidiasis remains a significant health problem globally. The host immune system at various levels uses pattern recognition receptors (PRRs) to identify candidal pathogen-associated molecular patterns (PAMPs). The defense aim at control using barriers, phagocytosis, secretory antimicrobial peptides (AMPs), complements, neutrophil extracellular traps (NETs), and the like. Of note, Candida devises a multitude of ways to overcome virtually all the protective strategies of the human host defense. Candida evades the host immune system using an array of mechanisms to establish infection. Evasive modalities include proteolytic enzymes, nutrient scavenging, and free radicals’ detoxification. Other methods involved concealment of PAMPs through shape shifting, diverting candidal recognition towards the production of anti-inflammatory cytokines. Here we review some of these host-pathogen interactions to aid the development of immunotherapies.